Blockchain Technology for Employee Verification and Background Checks in the Human Resources Recruitment Process - Aditia Putra Hamid; Edi Sugiono; Hasanudin (MultiTech Publisher, 2024)
Blockchain technology offers an innovative solution for employee verification and background checks in the human resources (HR) recruitment process. This research aims to explore the application of blockchain technology in employee verification and background checks in the human resource (HR) recruitment process through prototype development and evaluation. This research methodology uses a qualitative approach with a focus on prototype design and testing. With a decentralised and transparent system, blockchain can reduce costs, increase trust, and protect personal data. The results show that the adoption of blockchain in recruitment can optimise operational efficiency and minimise the risk of data fraud.